Coloring Adenolynphography and lymphatic system inguinopelvico - Lagrutta, J. (2015)
The authors propose a modification to the technique of lymphography by the addition to a radioactive isotope (I 131) of a vegetable colorant that permits the direct observation of the lymphatic tract during the surgical exploration.